IDENTIFICATION OF TROPICAL SQUALL LINE USING INFRARED CHANNEL HIMAWARI-8 SATELLITE IMAGERY (CASE STUDY OF 6-7 DECEMBER 2020 IN THE INDIAN OCEAN) - Nurul Izzah Fitria; Novvria Sagita; Arnelia Indah Cahyani (Jurnal Meteorologi dan Geofisika, 2022)
Tropical squall line is a linear type of Mesoscale Convective Systems (MCS) phenomenon. On December 6-7, 2020, the Infrared (IR1) Himawari-8 satellite image in the Indian Ocean of Indonesian region, shows a cloud line identified as the tropical squall line. This study aims to identify the characteristics of the tropical squall line phenomenon that occurs in the Indian Ocean south of West Java using Himawari-8 Infrared (IR1) satellite imagery. Satellite image data is processed using an algorithm adapted to the MCC Maddox 1980 criteria. Furthermore, an objective analysis is carried out on the data based on the criteria from previous studies. The result shows that the tropical squall occurred for 19 hours with the initial type of tropical squall formation as intersecting convective band. In the mature stage, the trailing stratiform region and convective line develops an asymmetric pattern and shows a vortex (Mesoscale Convective Vortices) that forms inside the stratiform region. The result of rainfall distribution using the GSMaP model shows a category of heavy rain with rainfall in tropical squall areas exceeding 10 mm per hour.